PROFESIONALISME GURU DAN PENINGKATAN MUTU PENDIDIKAN DI ERA OTONOMI DAERAH - Nova Arianti; Hendrizal; Ira Maya Sofa; Rahma Yuni; Ramayulis Rahman; Rahayu Rahmadani; Ratna Juita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the relationship between teacher professionalism and education quality in Indonesia, especially in the context of regional autonomy. The issues raised include the challenges faced by the education system, such as inequitable access to education and teaching quality. The methodology used is a qualitative approach with data collection through interviews and surveys of teachers, students and education stakeholders in several regions. The results show that there is a significant relationship between teacher professionalism and improving the quality of education, where teachers who have good pedagogical competence and professional attitudes are able to create a conducive learning environment. In addition, factors such as adequate education facilities and parental and community involvement also contribute to student learning outcomes. This study recommends improving the quality of teacher training, developing equitable education policies and improving teachers' welfare to support their professionalism. The findings are expected to contribute to the development of more effective education policies in Indonesia.